A Scientific Learning Model for Interest and Science Process Skills - M. Dwi Wiwik Ernawati; Asrial Asrial; Rahmat Perdana; Wahyu Adi Pratama; Sabila Eka Septi (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2022)
This research was conducted with the aim of knowing the differences in science process skills and student interest in science subjects regarding environmental pollution with project based learning and problem solving models for students in grades 7A and 7 B at SMPN 8 Muaro Jambi. This research is a survey research, this study uses quantitative data analysis with the help of SPSS statistics 25, to find descriptive statistics , test assumptions and test hypotheses . The results obtained from this study with a sample of 70 students from SMPN 8 Batanghari in Batanghari district. The subjects taken were grades 7A and 7 B which consisted of 40 women and 30 men. Based on the T-test of science process skills and students' interest in the science subject matter of environmental pollution with the project based learning model and problem solving for students in grades 7A and 7 B, it was concluded that there were differences in science process skills and students' interest in science subjects with the model project based learning and Problem Solving students in grades 7A and 7 B.